2019
DOI: 10.35410/ijaeb.2019.4424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bagging Time on Fruit Quality and Shelf Life of Mango (Mangifera Indica L.) Cv. Langra in Bangladesh

Abstract: The present experiment titled "pre harvest bagging enhanced quality and shelf life of mango cv. Langra" was conducted during the year 2017 at the mango orchard near Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh. The research was carried out in the Randomized Complete Block Design with three replications. Mango fruits were bagged at 35, 45 and 55 days after fruit set with different types of bags which constituted various treatments viz.: T1: Transparent polythene bag, T2: White p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
4
10
0
1
Order By: Relevance
“…During ripening stage, white paper bag exhibited maximum total sugar (5.96%) whereas minimum (4.00%) was recorded in polythene bag (Table 3). These results are very close to the earlier findings [31,4]. They reported that bagged fruits of mango and palm exhibited the maximum total sugars at ripening stage (Table 3).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…During ripening stage, white paper bag exhibited maximum total sugar (5.96%) whereas minimum (4.00%) was recorded in polythene bag (Table 3). These results are very close to the earlier findings [31,4]. They reported that bagged fruits of mango and palm exhibited the maximum total sugars at ripening stage (Table 3).…”
Section: Resultssupporting
confidence: 92%
“…Pre-harvest fruit bagging has been widely used in various fruit crops, such as mango [3,4,16], apple [17], pear [18], peach [19], to enhance the commercial standard of the fruit, namely, promoting fruit coloration [20], reduces mechanical damage [21] and sunburn [22] of the skin. Pre-harvest bagging also reduces the use of pesticides in the fruit and controlling insect [23], disease [24] and bird damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several good agricultural practices are becoming popular throughout the world for preventing the losses of fruits caused by both biotic and abiotic factors [4]. Among several such alternatives, the pre-harvest fruit bagging technique has been adopted widely in several fruit crops to improve skin color in the same time, to reduce the incidence of diseases, insect pests, mechanical damages, sunburn of the skin, agrochemical residues on the fruits, and bird damages [5,6,7,8,9,10,11,12,13]. Therefore, the present study has been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Among several such alternatives, Pre-harvest paper bagging is a physical protection method which not only improves the visual quality of fruit by promoting skin coloration and reducing blemishes, but can also change the microenvironment for fruit development, which can have several beneficial effects on internal fruit quality. Pre-harvest bagging of fruit can also reduce the incidence of disease, insect pest and/or mechanical damage, sunburn of the skin, fruit cracking, agrochemical residues on the fruit, and bird damage [3,4,5,6,7,8,9,10]. The aim of this study was undertaken to control mango pests and diseases as well as to improve the fruit quality of mango through bagging technology.…”
Section: Introductionmentioning
confidence: 99%